GMab-1, a high-affinity anti-3'-isoLM1/3',6'-isoLD1 IgG monoclonal antibody, raised in lacto-series ganglioside-defective knockout mice - Kato, Yukinari (2009)
The lacto-series gangliosides 3'-isoLM1 and 3',6'-isoLD1 have been identified as tumor-associated antigens whose formation is initiated by the Lc3 synthase. Until now, high- affinity IgG monoclonal antibodies (mAbs) against 3'-isoLM1 and 3',6'-isoLD1, which are highly expressed in gliomas, have not been developed, although mAbs against lacto-series gangliosides are powerful tools for functional studies. We recently produced the Lc3-synthase gene β3Gn-T5 knockout mice. In this study, we immunized β3Gn-T5 knockout mice with 3'-isoLM1/3',6'-isoLD1 and produced the anti-3'-isoLM1/3',6'-isoLD1 mAb GMab-1, of the IgG(3) subclass, which should be useful for functional analysis of lacto-series gangliosides and for antibody-based therapy of gliomas.